Retrospective and prospective assessment of butorphanol, azaperone and medetomidine (BAM™) for immobilisation of feral horses (Equus ferus caballus). (26th July 2021) - Balko, Julie A.; Fogle, Callie; Stuska, Susan J.; Fogle, Jonathan E.; Posner, Lysa P.
Abstract: Background: Butorphanol–azaperone–medetomidine (BAM™) has not been evaluated in horses. Objectives: The objective of this study was to evaluate BAM™ for chemical restraint of feral horses. Study design: Retrospective and prospective descriptive studies. Methods: Data were collected retrospectively from medical records of 28 feral horses immobilised with BAM™ over a 6‐year period. Prospectively, 0.0125 mL/kg bwt of BAM™ (butorphanol 27.3 mg/mL, azaperone 9.1 mg/mL and medetomidine 10.9 mg/mL) intramuscularly (im) was administered to eight stallions via dart, and once recumbent, 1.0 mg/kg bwt ketamine was given intravenously (iv). Induction and recovery time and quality via a standardised rubric (1 =  very poor ; 5 =  excellent ) and visual analogue scale (VAS), need for additional darts, weight tape measurement and serial physiological parameters were recorded. Serial arterial blood gas analysis was performed during recumbency. Following castration, horses were given 0.1 mg/kg bwt atipamezole (25% iv and 75% im) and allowed to recover unaided. Results: Retrospectively, 28 horses were successfully immobilised with BAM™ without a major complication. Prospectively, eight horses were given a median (range) actual BAM TM dose of 0.0143 (0.0127‐0.0510) mL/kg bwt. Three of eight horses needed 1, 2 or 5 additional darts. Median (range) time to recumbency was 11 (2‐44) minutes. Median (range) induction (n = 4) and recovery (n = 6) scores via rubric and VAS were 5 (4‐5) and 5 (5‐5) and 92 (86‐93) and 98 (92‐99) cm, respectively. Four of seven horses were hypoxaemic at ≥1 time point with otherwise acceptable physiological parameters. Following atipamezole, median (range) time to sternal recumbency and standing was 12 (2‐18) and 17 (11‐52) minutes, respectively (n = 6). Main limitations: The sample size was small. Data could not be collected before darting or after recovery. Some data were missing from retrospective analysis. Conclusions: Intramuscular BAM™ with iv ketamine provided chemical restraint suitable for field castration of feral horses with no mortality. Hypoxaemia occurred in the majority of horses.